2015
DOI: 10.1007/s11368-015-1310-4
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of macro, micro, and toxic element uptake by Salix × smithiana using liming of heavily contaminated soils

Abstract: Purpose Willow cultivation in soils heavily contaminated by risk elements is a challenging issue due to phytotoxic effects that restrict plant growth. Liming reduces the mobility of some risk elements in contaminated soils and therefore can be a suitable measure for contaminated soils but can also affect availability of nutrients for planted willows. We investigate how liming affects concentrations of macro, micro, and toxic elements in the organs of willows planted in contaminated soils. Materials and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…The Cd accumulation capability of different woody plants is different and that in different parts of the same kinds of woody plants are also different [4]. Concentrations of Cd and other elements are almost significantly higher in the roots than in above-ground tissues [18]. Data from the present investigation indicated that S. matsudana had the ability to accumulate Cd primarily in their roots (about 70%), with lower concentrations in the shoots.…”
Section: Discussionmentioning
confidence: 66%
“…The Cd accumulation capability of different woody plants is different and that in different parts of the same kinds of woody plants are also different [4]. Concentrations of Cd and other elements are almost significantly higher in the roots than in above-ground tissues [18]. Data from the present investigation indicated that S. matsudana had the ability to accumulate Cd primarily in their roots (about 70%), with lower concentrations in the shoots.…”
Section: Discussionmentioning
confidence: 66%